The Influence of Satisfaction and Trust on Online Purchase Decision - Muslikh Muslikh; Zainal Zainal; Rini Hidayati (Jurnal Akuntansi, Manajemen dan Ekonomi, 2017)
The purpose of this study is to determine the effect of consumer satisfaction and trust on buying attitude and its impact on online purchase decision. The study was conducted through survey by distributing questionnaires to 130 students in Jakarta from various faculties. Research sampling used non probability sampling with purposive sampling technique. The results showed that: consumer satisfaction and trust have positive and significant effect on online purchase attitude. Consumer satisfaction and trust have positive and significant effect on online purchase decision, purchase attitude has significant effect on online purchase decision.